Implementation of a quality control for radio occultation observations in the presence of large gradients of atmospheric refractivity - L. Cucurull (Atmospheric Measurement Techniques, 2015)
In preparation for the launch of the first six satellites of the COSMIC-2 mission in equatorial orbit, and the larger number of observations that such a mission will provide in the lower tropical troposphere, work is underway at the National Oceanic and Atmospheric Administration (NOAA) to improve the assimilation of radio occultation (RO) observations, particularly in the lower tropical troposphere. As part of the improvement of the bending angle forward operator at the National Centers for Environmental Prediction (NCEP), additional quality controls aimed to detect and reject observations that might have been affected by super-refraction conditions have been implemented and tested. The updated quality control procedures also address the situation where the model detects atmospheric super-refraction conditions. This paper describes the limitations of the current standard quality controls and discusses the implementation of additional quality control procedures to address the limitations of assimilating observations likely affected by the super-refraction conditions, either in the model simulation or in the retrieval process.